2007
DOI: 10.1186/1742-2094-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the alternative complement activation pathway in traumatic brain injury by a monoclonal anti-factor B antibody: a randomized placebo-controlled study in mice

Abstract: Background: The posttraumatic response to traumatic brain injury (TBI) is characterized, in part, by activation of the innate immune response, including the complement system. We have recently shown that mice devoid of a functional alternative pathway of complement activation (factor B-/-mice) are protected from complement-mediated neuroinflammation and neuropathology after TBI. In the present study, we extrapolated this knowledge from studies in genetically engineered mice to a pharmacological approach using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 47 publications
2
98
0
Order By: Relevance
“…However, these analyses do not distinguish between the possibilities that any of these traditional upstream pathways may be sufficient to activate C3 and promote normal liver regeneration or, alternatively, that non-traditional mechanisms activate complement signaling during liver regeneration. To investigate these considerations, the hepatic regenerative response was evaluated in C4-null mice treated with a well characterized anti-factor B neutralizing monoclonal antibody (mAb 1379, (Leinhase et al 2007; Taube et al 2006;Thurman et al 2005). In these animals, the classical and lectin-dependent pathways are blocked by genetic disruption of C4 expression (Figure 1) while the alternative pathway is entirely suppressed by the neutralizing antibody ( Figure 4B).…”
Section: Liver Regeneration and C3 Activation Occur Normally In C4-numentioning
confidence: 99%
“…However, these analyses do not distinguish between the possibilities that any of these traditional upstream pathways may be sufficient to activate C3 and promote normal liver regeneration or, alternatively, that non-traditional mechanisms activate complement signaling during liver regeneration. To investigate these considerations, the hepatic regenerative response was evaluated in C4-null mice treated with a well characterized anti-factor B neutralizing monoclonal antibody (mAb 1379, (Leinhase et al 2007; Taube et al 2006;Thurman et al 2005). In these animals, the classical and lectin-dependent pathways are blocked by genetic disruption of C4 expression (Figure 1) while the alternative pathway is entirely suppressed by the neutralizing antibody ( Figure 4B).…”
Section: Liver Regeneration and C3 Activation Occur Normally In C4-numentioning
confidence: 99%
“…For example, peroxisome proliferator-activated receptors have recently emerged as potent antiinflammatory transcription factors that when used alone or in combination with endocannabinoids may prove to be pivotal antiinflammatory and neuroprotective agents in the setting of TBI (124,125). In addition, selective targeting of the innate immune response after trauma, such as by pharmacological inhibition of the complement cascade at various levels of its activation pathways, has recently emerged as a new promising therapeutic strategy in experimental TBI models (126)(127)(128)(129). Exciting treatment possibilities such as these promise a riveting future for research in the treatment of TBI.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, blockade of C3 activation in a mouse model of microglia priming reversed priming and suppressed experimental autoimmune encephalitis (EAE)-induced inflammation [8]. Studies from other groups have also shown that inhibition of C3 activation via the alternative pathway is protective in the experimental mouse model of closed head injury [60,62]. The complement system plays a vital role because it is the first line of defence against pathogens; it generates chemoattractants for inflammatory cells, facilitates solubilisation and clearance of opsonised immune complexes, mediates cell lysis, and influences adaptive immunity [150,151].…”
Section: Therapeutical Targetsmentioning
confidence: 96%
“…Mice deficient in the C3 or C5 components subjected to traumatic brain cryoinjury showed reduced neutrophils and secondary tissue damage compared to their wildtype littermates [58]. TBI on fB -/-transgenic mice or mice treated with a monoclonal anti-fB antibody showed reduced posttraumatic neuronal cell death, a strong upregulation of the anti-apoptotic mediator Bcl-2 and downregulation of the pro-apoptotic Fas receptor compared to the fB +/+ littermates, implicating the alternative complement pathway in the progression of the secondary neuronal death [59,60]. Neurological function after TBI was improved in transgenic mice with brain-targeted overexpression of complement receptor 1-related protein y (Crry), a potent inhibitor of the C3 convertase [61] or in mice treated with a recombinant Crry molecule (Crry-Ig) in which Crry is fused to the non-complement fixing mouse IgG1 Fc region [62].…”
Section: Microscopic Neuropathological Changesmentioning
confidence: 99%